2023
DOI: 10.3390/su152015056
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects of Driver Distraction at Traffic Lights: Mobile Phone Use

Kadir Diler Alemdar,
Merve Kayacı Çodur,
Muhammed Yasin Codur
et al.

Abstract: The transportation demands of people are increasing day by day depending on the population, and the number of vehicles in traffic is causing various problems. To meet the energy needs of vehicles, there is a huge burden on countries in terms of fossil fuels. In addition, the use of fossil fuels in vehicles has a serious impact on environmental pollution. Various studies have been carried out to prevent unnecessary fuel consumption and emissions. Behavior of drivers, who are important components of traffic, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Driver behavior, such as acceleration patterns, speed, and gear-shifting practices, also significantly affects fuel consumption. For example, in the study of Alemdar et al [11] an additional behavioral factor is examined-driver distraction, particularly through mobile phone use at traffic lights. This study demonstrated that distractions lead to delayed responses when lights turn green, causing unnecessary idling, increased fuel consumption, and higher emissions.…”
Section: Factors Affecting Fuel Consumptionmentioning
confidence: 99%
“…Driver behavior, such as acceleration patterns, speed, and gear-shifting practices, also significantly affects fuel consumption. For example, in the study of Alemdar et al [11] an additional behavioral factor is examined-driver distraction, particularly through mobile phone use at traffic lights. This study demonstrated that distractions lead to delayed responses when lights turn green, causing unnecessary idling, increased fuel consumption, and higher emissions.…”
Section: Factors Affecting Fuel Consumptionmentioning
confidence: 99%
“…Furthermore, the examination of individual traits revealed that education levels and prior accident experiences had the most effects on the self-reported aggressive driving behavior (SADB) and the subjective assessment of others' aggressive driving behavior OADB). In another study, the effects on fuel consumption and emissions of drivers being distracted by their phones at traffic signals were studied by Alemdar, Kayacı Çodur [31]. Roadside observations at crossroads in Turkey's Erzurum Province were used for the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, the study discovered that at the chosen crossings, these diversions led to an annual fuel use of roughly 177,025 L and emissions of 0.294 kg of NO x and 251.68 kg of CO 2 . The study emphasizes the necessity of education and actions to lessen the negative effects that certain driving practices have on the environment and the economy [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, driver distraction detection is of great significance for improving road safety, preventing traffic accidents, and promoting the development of intelligent transportation systems [4]. By reducing driver distraction, we can create a safer, more efficient, and sustainable road transportation environment [5].…”
Section: Introductionmentioning
confidence: 99%